Design potential selective inhibitors for human leukocyte common antigen-related (PTP-LAR) with fragment replace approach. Issue 18 (11th December 2020) - Wu, Jing-Wei; Zhang, Huan; Li, Wei-Ya; Tang, Xue; Li, Hong-Lian; Lu, Xin-Hua; Zheng, Zhi-Hui; Ma, Ying; Wang, Run-Ling
Abstract: The overexpression of PTP-LAR could cause the insulin resistance, so PTP-LAR might be a promising target for treating diabetes. In this study, we applied the computer modeling methods with fragment replace approach to screen the fragment database by targeting PTP domain and site B with the aim to discover potent and selective PTP-LAR inhibitors. A series of novel 4-thiazolidone derivatives were gained. The results of their ADMET predictions indicated that these new compounds might become drug candidates. The series of these derivatives were synthesized. Subsequently, their PTP-LAR inhibitory activities were assayed. The compound7d showed highly selectivity for PTP-LAR (10.41 μM) over its close homolog PTP1B (IC50 =44.40 μM), SHP2 (IC50 >122.81 μM) and CDC25B (IC50 >122.81 μM) and docking and molecular dynamics simulation were applied to propose the most likely binding mode of compound7d with PTP-LAR. Thus, our findings reported here may pave a way for discovering potential selective PTP-LAR inhibitors. Abbreviations: PTP-LAR Human leukocyte common antigen-related PTP Protein Tyrosine Phosphatase IR insulin receptor PTP1B Protein tyrosine phosphatase-1B LRP Lung resistance protein ADMET absorption, distribution, metabolism, excretion, toxicity PPB plasma protein binding BBB blood brain barrier penetration CYP450 cytochrome P450 HIA human intestinal absorption TLC thin-layer chromatography UV Ultra Violet NMR nuclear magnetic resonance TMS tetramethylsilane MS mass spectrometry ANM anisotropic network mode PDB Protein Data Bank DMF N, N-Dimethylformamide pNPP para-nitrophenyl phosphate DTT dithiothreitol MD molecular dynamic RMSD root-mean-square deviation RMSF root-mean-square fluctuation SPC single-point charge PME Particle Mesh Ewald MM-PBSA molecular mechanics Poisson Boltzmann surface area H bond, hydrogen bond VDW Van der Waals Communicated by Ramaswamy H. Sarma